2012
DOI: 10.1002/lary.23443
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and incidence of salivary leak following laryngectomy

Abstract: Objectives/Hypothesis To determine the incidence and risk factors of pharyngocutaneous fistula formation in patients undergoing either primary or salvage laryngectomies and evaluate the role of barium esophagram in these patients. Study Design Retrospective cohort study. Methods Medical records of 259 patients who underwent total laryngectomy between 2003 and 2009 at our institution were reviewed. Risk factors for fistula formation were analyzed, including primary treatment modality, comorbidities, and ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
116
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(129 citation statements)
references
References 19 publications
9
116
2
2
Order By: Relevance
“…In our study, we demonstrated an increased incidence of PCF in patients with preoperative RT, which is in agreement with the majority of literature reports (13)(14)(15)(16)(17)(18)(19)(20). While, some studies did not find any association between preoperative RT and PCF formation (5-7, 21, 22).…”
Section: Discussionsupporting
confidence: 92%
“…In our study, we demonstrated an increased incidence of PCF in patients with preoperative RT, which is in agreement with the majority of literature reports (13)(14)(15)(16)(17)(18)(19)(20). While, some studies did not find any association between preoperative RT and PCF formation (5-7, 21, 22).…”
Section: Discussionsupporting
confidence: 92%
“…This has been reported in other studies [22,23] and also in a meta-analysis [7], and there is speculation that it may be secondary to tissue contamination and/or larger tumor size [22]. We also identified hypothyroidism and low postoperative hemoglobin as risk factors for PCF, which have consistently been reported in other studies [7,13,14,19,23]. …”
Section: Discussionsupporting
confidence: 87%
“…Preoperative radiation therapy increases both the frequency and severity of postoperative PCF [3,4,10,1315], and chemotherapy augments this effect [3,16,17]. Other factors associated with increased rates of PCF include patient comorbidities [8,10,18], hypothyroidism [13], low perioperative hemoglobin [7,19,20] and albumin [10,19], more advanced primary tumor stage [21], prior tracheotomy [7,22,23] positive surgical margins [24,25], concurrent neck dissection [7,15,18], shorter elapsed time from completion of radiation to surgery [15], and surgical closure technique [10,12,26]. Although it is generally accepted that previous radiation and chemoradiation increase the risk of PCF [27], there is little consensus regarding the relative significance of these other various factors.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review by White HN et al [13] showed pharyngocutaneous fistula overall incidence of 21 %. Their data confirmed previous radiotherapy and hypothyroidism, particularly in salvage laryngectomy patients, as important significant predictors of postoperative pharyngocutaneous fistula.…”
Section: Discussionmentioning
confidence: 99%